The effectiveness of behavioural interventions in the primary prevention of Hepatitis C amongst injecting drug users: a randomised controlled trial and lessons learned - Tibbs Christopher; Corrin Betsy; John Christopher; Godfrey Christine; Maxwell Douglas; Drummond Colin; Checinski Ken; Rice Philip; Davis Paul; Abou-Saleh Mohammed; Oyefeso Adenekan; de Ruiter Marian; et al. (BMC, 2008)
Abstract Aim To develop and evaluate the comparative effectiveness of behavioural interventions of enhanced prevention counselling (EPC) and simple educational counselling (SEC) in reducing hepatitis C viral (HCV) infection in sero-negative injecting drug users (IDU). Design Randomised controlled trial (RCT) of EPC intervention in comparison with simple educational counselling (SEC). Setting Specialised Drug services in London and Surrey, United Kingdom. Participants and Measurements Ninety five IDUs were recruited and randomised to receive EPC (n = 43) or SEC (n = 52). Subjects were assessed at baseline using the Addiction Severity Index (ASI), the Injecting Risk Questionnaire (IRQ), and Drug Injecting Confidence Questionnaire (DICQ). The primary outcome was measured by the rate of sero-conversion at 6 months and 12 months from baseline and by the ASI, IRQ and DICQ at 6 months from baseline. Hepatitis C testing was undertaken by the innovative test of the dried blood spot (DBS) test which increased the rate of testing by 4 fold compared to routine blood testing. Findings Seventy Eighty two subjects (82%) out of the 95 recruited were followed up at 6 months and 62 (65%) were followed up at 12 months. On the primary outcome measure of the rate of seroconversion, 8 out of 62 patients followed-up at twelve months seroconverted, three in the EPC group and five in the SEC group, indicating incidence rates of 9.1 per 100 person years for the EPC group, 17.2 per 100 person years for the SEC group, and 12.9 per 100 person years for the cohort as a whole. Analysis of the secondary outcome measures on alcohol use, risk behaviour, psychological measures, quality of life, showed no significant differences between the EPC and the SEC groups. However, there were significant changes on a number of measures from baseline values indicating positive change for both groups. Conclusion We were not able to prove the efficacy of EPC in comparison with SEC in the prevention of hepatitis C in IDUs. This was related to low recruitment and retention rates of the participants. Moreover there was a low adherence rate to EPC. The study provided the benefits of developing and introducing behavioural interventions of the EPC and SEC and the DBS screening for Hepatitis C. Moreover the main lessons learnt were that piloting of a new intervention is a crucial first step before conducting pragmatic RCTs of psychological interventions in the field of addiction; that an infrastructure and culture for psychosocial interventions is needed to enable applied research in the service environment, and research funding is needed for enabling the recruitment of dedicated trained therapists for the delivery of these interventions.